Pyran-bridged A-D-A type small molecular acceptors for organic solar cells. (1st May 2019) - Liu, Zhitian; Zhang, Xiaolu; Ren, Peng; Wu, Yao; Zeng, Di; Duan, Xianbao; Gao, Xiang; Cai, Ping
Highlights: Pyran-bridged fused-ring is a promising unit to construct nonfullerene acceptors. The effects of π-bridge and terminal groups were systematically studied. Pyran-bridged nonfullerene acceptors exhibit wider absorption spectra. Abstract: Pyran is fused into the planar donor moiety to enhance the extinction coefficient and reduce the bandgap, thus two acceptors PTTIC and PTBT-R are designed and synthesized. Compared to the IDT-based acceptor, these pyran-bridged acceptors show higher the highest occupied molecular orbital level and wider absorption coverage. Devices fabricated with poly[(2, 6-(4, 8-bis(5-(2-ethylhexyl)thiophen-2-yl)benzo[1, 2-b:4, 5-b′]dithiophene)-co-(1, 3-di(5-thiophene-2-yl)-5, 7-bis(2-ethylhexyl)-benzo[1, 2-c:4, 5-c′]dithiophene-4, 8-dione)] (PBDB-T):PTTIC as the active layer give a power conversion efficiency (PCE) of 7.35%.